Demands of English teacher competencies: Input for curriculum development at the University - Nur Fadillah Nurchalis (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2020)
To guarantee that alumni of a university can be accepted in the market, thus it is necessary to observe the demands of English teacher’s users. This research is expected to become input for curriculum development at English study program of STAIN Majene. Hence, this present study was designed by using descriptive qualitative. The informants of this research were two principals, two English teachers, and two students who represent urban and rural schools in Majene, West Sulawesi, Indonesia. They are users of English teacher candidates. This research used an in-depth interview to gain data. The data analyzed using the Huberman model, namely data reduction, data display, and conclusion drawing.  The results showed that what principals, English teachers and students need regarding the profile of future English teachers based on teaching competence are as follow: 1) talented teachers who have a bunch of teaching experiences in the various situation; 2) English teachers who are able to brand themselves as educators, trainers, coaches, evaluators, etc; 3) English teachers who have good communication competence; 4) English teachers who are fluent in speaking English; and 5) English teachers who have good IT literacy in teaching. Therefore, credits of teaching practice, teacher professionalism, communication ethics, and speaking skill courses should be maximized.Keywords: English teacher, teacher competence, users’ demands DOI: 10.26905/enjourme.v5i2.4971